Sosialisasi Digital Parenting Terhadap Penyalahgunaan IT Pada Anak-anak di Desa Sampiro - Putra, Edson; Tombeng, Marchel; Ibrahim Adam, Stenly; Herawan Moedjahedy, Jimmy (Universitas Klabat, 2024)
The author carried out this community service in Sampiro village, Sangkub subdistrict, North Bolaang Mongondow district, North Sulawesi province together with students who are members of the Maranatha Unklab evangelism group. Carried out over a period of 10 days with many programs carried out, one of which is providing digital parenting outreach to parents in Sampiro village with the aim of ensuring that parents have digital literacy and provide supervision and control to children in using cellphones to avoid deviations. The method used is tiered qualitative, conducting interviews, in-depth research and outreach to each party starting from the village head, to the children and finally to the parents. The results obtained were that the children of Sampiro village all used cellphones, although not all of them had their own. The majority, namely 85%, play games, both online and offline games, and the majority, 65%, already have social media accounts. And children admit that their parents often remind them about using cellphones. Meanwhile, on the parents' side, the results showed that not all parents understood how to limit children's use of cellphones, even though most parents could afford cellphones. The conclusion is that the people of Sampiro village still need a lot of understanding on how to limit children's use of cellphones.